A Phase I Study to Investigate the Safety, Tolerability and Pharmacokinetics of Napabucasin Combined with Sorafenib in Japanese Patients with Unresectable Hepatocellular Carcinoma - Takuji Okusaka; Manabu Morimoto; Yuichiro Eguchi; Shinichiro Nakamura; Shuichi Iino; Rie Kageyama (Adis, Springer Healthcare, 2023)
Abstract Background and Objective For patients with advanced hepatocellular carcinoma (HCC), the standard of care for many years has been sorafenib. Preliminary data have suggested that the combination of the NAD(P)H:quinone oxidoreductase 1 bioactivatable agent napabucasin plus sorafenib may improve clinical outcomes in patients with HCC. In this phase I, multicenter, uncontrolled, open-label study, we evaluated napabucasin (480 mg/day) plus sorafenib (800 mg/day) in Japanese patients with unresectable HCC. Methods Adults with unresectable HCC and an Eastern Cooperative Oncology Group performance status of 0 or 1 were enrolled in a 3 + 3 trial design. The occurrence of dose-limiting toxicities was assessed through 29 days from the start of napabucasin administration. Additional endpoints included safety, pharmacokinetics, and preliminary antitumor efficacy. Results In the six patients who initiated treatment with napabucasin, no dose-limiting toxicities occurred. The most frequently reported adverse events were diarrhea (83.3%) and palmar-plantar erythrodysesthesia syndrome (66.7%), all of which were grade 1 or 2. The pharmacokinetic results for napabucasin were consistent with prior publications. The best overall response (per Response Evaluation Criteria in Solid Tumors [RECIST] version 1.1) was stable disease in four patients. Using Kaplan-Meier methodology, the 6-month progression-free survival rate was 16.7% per RECIST 1.1 and 20.0% per modified RECIST for HCC. The 12-month overall survival rate was 50.0%. Conclusions These findings confirm the viability of napabucasin plus sorafenib treatment, and there were no safety or tolerability concerns in Japanese patients with unresectable HCC. Clinical Trial Registration ClinicalTrials.gov identifier NCT02358395, registered on 9 February 2015.